Halogen-free flame-retardant regenerated PET material for steel coil packaging and preparation method of halogen-free flame-retardant regenerated PET material

By adding POE-g-GMA, toughener and polyethylene terephthalate-1,4-cyclohexanedimethanol fat to the regenerated PET material, chemical bonds and crosslinked structures are formed, which solves the problems of low impact strength and poor flame retardant performance of regenerated PET materials, and achieves efficient steel coil packaging protection.

CN119752132AActive Publication Date: 2025-04-04WUHAN TAIXING METALLURGY MATERIAL CO LTD

Patent Information

Application Number
CN202510022329.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-07
Publication Date
2025-04-04
Estimated Expiration
2045-01-07

AI Technical Summary

Technical Problem

The molecular chain breaks during mechanical recycling, resulting in a decrease in mechanical properties, especially the impact strength, and its flame retardant properties, which cannot effectively protect the steel coil during storage and transportation.

Method used

Halogen-free flame-retardant regenerated PET material is used to melt extrude the regenerated PET with POE-g-GMA, toughener, and polyethylene terephthalate-1,4-cyclohexanedimethanol fat to form chemical bonds and crosslinked structures, thereby improving the impact resistance and flame retardant effect of the material.

Benefits of technology

It significantly improves the impact resistance and flame retardant effect of recycled PET materials, enhances the compatibility and stability of the materials, and ensures the safety and reliability of the steel coil packaging.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005231751410000111
    Figure BDA0005231751410000111
  • Figure BDA0005231751410000121
    Figure BDA0005231751410000121
Patent Text Reader

Abstract

The invention discloses a halogen-free flame-retardant regenerated PET material for steel coil packaging and a preparation method thereof, and belongs to the technical field of regenerated PET materials, and the halogen-free flame-retardant regenerated PET material for steel coil packaging is characterized by comprising the following raw materials in parts by weight: 100 parts of regenerated PET, 5-10 parts of POE-g-GMA, 4-8 parts of a flexibilizer, 1-3 parts of polyethylene glycol terephthalate, 1-3 parts of a flame retardant, 1-3 parts of an antioxidant, 1-3 parts of a lubricant, and 1-3 parts of a lubricant. The regenerated PET material is prepared from the following components in parts by weight: 15-20 parts of 1, 4-cyclohexanedimethanol ester, 3-7 parts of a flame retardant, 1-3 parts of a stabilizer and 0.3-0.5 part of an antioxidant, so that the effect of improving the impact resistance of the regenerated PET material is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of recycled PET materials, and in particular to a halogen-free flame-retardant recycled PET material for steel coil packaging and a preparation method thereof. Background Art

[0002] High-quality steel coils such as metallurgical cold-rolled plates, galvanized plates, tin-coated plates, color-coated plates, and silicon steel plates have large weight and inertia. During transportation, the outer edges of both ends of the steel coils are easily damaged by impact. Once the two ends of the steel coils are impacted, the deformation of the ends of the steel coils will affect the quality of the steel plates. Therefore, the protection of the steel coils during storage and transportation is particularly important.

[0003] PET (polyethylene terephthalate) is widely used in chemical fiber, packaging and plastic modification due to its excellent mechanical properties, good processing and molding, high chemical stability and other advantages. In recent years, with the enhancement of environmental awareness, the recycling of waste PET materials has gradually increased. During the mechanical recycling process of PET materials, the PET molecular chain will break, resulting in a decrease in its molecular weight and deterioration of its mechanical properties. Among them, the impact strength of recycled PET materials will be significantly lower than that of virgin PET materials, which will eventually increase the brittleness of PET material products. In addition, during the combustion process of PET materials, serious melting droplets will occur and a large amount of heat will be released. Its flame retardant performance is relatively poor. Therefore, when recycled PET materials are used in steel coil packaging, they cannot protect the steel coil well. Summary of the invention

[0004] In order to improve the impact resistance of recycled PET materials, the present invention provides a halogen-free flame-retardant recycled PET material for steel coil packaging and a preparation method thereof.

[0005] The first aspect of the present invention is to provide a halogen-free flame-retardant recycled PET material for steel coil packaging, which adopts the following technical scheme:

[0006] A halogen-free flame-retardant recycled PET material for steel coil packaging comprises the following raw materials in parts by weight: 100 parts of recycled PET, 5-10 parts of POE-g-GMA, 4-8 parts of a toughening agent, 15-20 parts of polyethylene terephthalate-1,4-cyclohexanedimethanol, 3-7 parts of a flame retardant, 1-3 parts of a stabilizer, and 0.3-0.5 parts of an antioxidant.

[0007] By adopting the above technical scheme, after the recycled PET is melt-extruded with POE-g-GMA, a toughening agent, and polyethylene terephthalate-1,4-cyclohexanedimethanol, the impact resistance of the recycled PET can be effectively improved. The reason is that during the melt blending process, the polar groups contained in POE-g-GMA react with the terminal groups in PET and polyethylene terephthalate-1,4-cyclohexanedimethanol to form chemical bonds, which increase the degree of cross-linking between the blends and form a copolymer with a higher molecular weight, thereby improving the compatibility and stability of the blends to a certain extent. In addition, the formation of chemical bonding greatly weakens the interfacial tension of the copolymer and prevents the occurrence of phase separation, thereby greatly improving the impact strength of the recycled PET material and effectively achieving the toughening effect. Therefore, the use of the toughening agent in combination with polyethylene terephthalate-1,4-cyclohexanedimethanol and POE-g-GMA can effectively ensure the tensile properties and impact resistance of the recycled PET material.

[0008] Preferably, the recycled PET is obtained by the following modification method, which comprises the following steps: drying the recycled PET particles, adding a silane coupling agent, mixing, melt extruding, cooling and pelletizing to obtain modified recycled PET, wherein the amount of the silane coupling agent added is 4-8% of the weight of the recycled PET.

[0009] Preferably, the silane coupling agent is isocyanatepropyltriethoxysilane.

[0010] By adopting the above technical scheme, after the recycled PET particles are modified with isocyanate propyl triethoxysilane coupling agent, the activity of the surface of the recycled PET particles can be enhanced, so that when the recycled PET particles come into contact with POE-g-GMA and polyethylene terephthalate-1,4-cyclohexanedimethanol, the interfacial interaction is enhanced, thereby improving the mechanical properties and processing stability of the recycled PET material.

[0011] Preferably, the toughening agent is obtained by the following preparation method:

[0012] S1. Mix 5 parts of butyl acrylate, 0.2 parts of propyl methacrylate, 0.5 parts of surfactant, 0.05 parts of ammonium persulfate, 0.05 parts of sodium bicarbonate and 30 parts of water by weight, and react at a temperature of 75±3°C for 30 minutes to obtain an emulsion;

[0013] S2. Add 5 parts of polyurethane prepolymer dropwise to the emulsion obtained in step S1 and add 0.35 parts of ammonium persulfate at the same time, react for 2 hours, cool, discharge and dry to obtain a toughening agent.

[0014] By adopting the above technical scheme, when the toughening agent is obtained by copolymerization of an acrylic copolymer and a polyurethane prepolymer, the compatibility of the toughening agent with the PET material can be effectively improved. At the same time, the addition of the toughening agent in the present application can reduce the ineffective destruction of the PET molecular chain and enhance the elasticity of the molecular chain, thereby more effectively transmitting and dispersing the impact energy and improving the impact resistance of the recycled PET material.

[0015] Preferably, the raw material also includes 2-5 parts of nano-wollastonite whiskers.

[0016] By adopting the above technical solution, the addition of nano-wollastonite whiskers enables the recycled PET material to absorb and disperse energy when receiving external force, thereby helping to enhance the toughness of the recycled PET and making the PET material less likely to break when impacted or stretched.

[0017] Preferably, the nano-wollastonite whiskers are modified nano-wollastonite whiskers, and the modification is obtained by the following method:

[0018] (1) Nano-wollastonite whiskers were ultrasonically dispersed in N,N-dimethylformamide, and then dimethylaminopyridine was added at 85°C and reacted at this temperature for 1 hour;

[0019] (2) adding dodecyl succinic anhydride dropwise to the reactant obtained in step (1), stirring the reaction for 4 hours after the addition is completed, and then cooling, washing, and drying the reactant to obtain modified nano-wollastonite whiskers.

[0020] By adopting the above technical scheme, the nano-wollastonite whiskers can be effectively improved in their dispersibility in the recycled PET material after being modified, and soft long-chain dodecyl succinic anhydride branches are grafted onto the surface of the nano-wollastonite whiskers, which can be entangled with PET molecules with the help of the flexible long-chain branches to obtain good interface bonding, so that when the recycled PET material is subjected to a large impact force, the force can be transferred from the bonding interface between the two to the nano-wollastonite whiskers, and more energy can be dissipated in the process, thereby further improving the impact resistance of the recycled PET material.

[0021] Preferably, the flame retardant is composed of a phosphorus-nitrogen intumescent flame retardant and diethyl zinc hypophosphite in a weight ratio of 1:(0.2-0.6).

[0022] Preferably, the phosphorus-nitrogen intumescent flame retardant is obtained by the following preparation method: 2-carboxyethylphenyl hypophosphorous acid and melamine in a molar ratio of 1:1 are added to water, the reaction is stirred at room temperature for 4.5-5 hours, the precipitate is filtered and washed, vacuum dried at 80±5°C for 5-6 hours, and heated at 160±5°C for 5 hours to obtain a white powder, which is washed again and vacuum dried at 80±5°C for 5-6 hours to obtain the phosphorus-nitrogen intumescent flame retardant.

[0023] By adopting the above technical scheme, when the flame retardant is composed of a phosphorus-nitrogen intumescent flame retardant and diethyl zinc hypophosphite, during the combustion process, the phosphorus-nitrogen intumescent flame retardant will decompose and generate a large amount of by-products such as phosphoric acid and metaphosphoric acid, which can catalyze the dehydration and carbonization of the polymer to form a stable carbon layer, and the nitrogen element in the phosphorus-nitrogen intumescent flame retardant will be released in the form of non-combustible gases such as ammonia, thereby diluting the oxygen concentration in the combustion area, taking away part of the heat, and reducing the combustion rate; while diethyl zinc hypophosphite will decompose during combustion to generate inorganic substances such as zinc phosphate, which have a high melting point and thermal stability, and can form a protective barrier on the surface of the material to prevent the further spread of the flame. At the same time, diethyl zinc hypophosphite can also capture free radicals generated during the combustion process, thereby inhibiting the progress of the chain reaction and slowing down the combustion rate. Therefore, after the phosphorus-nitrogen intumescent flame retardant and diethyl zinc hypophosphite are mixed, the two will cooperate with each other during the combustion process, and the carbon layer formed when the phosphorus-nitrogen intumescent flame retardant burns can provide attachment points for diethyl zinc phosphate, enabling it to better adhere to the surface of the polymer, while the protective barrier formed by diethyl zinc phosphate can further enhance the stability of the carbon layer formed when the phosphorus-nitrogen intumescent flame retardant burns, effectively improving the flame retardant effect of the recycled PET material.

[0024] Preferably, the stabilizer is methyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate.

[0025] By adopting the above technical scheme, when 3-(3,5-di-tert-butyl-4-hydroxyphenyl) methyl propionate is used as the stabilizer, during the melt blending process, the hydroxyl and carboxyl groups on 3-(3,5-di-tert-butyl-4-hydroxyphenyl) methyl propionate react with the active groups in the recycled PET particles, POE-g-GMA, and polyethylene terephthalate-1,4-cyclohexanedimethanol, thereby achieving a balance between the flexibility and rigidity of the recycled PET material, so that the recycled PET material has good tensile properties and impact resistance. In addition, after 3-(3,5-di-tert-butyl-4-hydroxyphenyl) methyl propionate is used as the stabilizer, the thermal stability of the recycled PET material can be effectively improved, thereby improving the heat resistance of the recycled PET.

[0026] Preferably, the antioxidant is one of dilauryl thiodipropionate and antioxidant 300.

[0027] The second aspect of the present invention is to provide a method for preparing a halogen-free flame-retardant recycled PET material for steel coil packaging, comprising the following steps: mixing recycled PET, POE-g-GMA, a toughening agent, polyethylene terephthalate-1,4-cyclohexanedimethanol, a flame retardant, a stabilizer and an antioxidant, and then melt-extruding to obtain a halogen-free flame-retardant recycled PET material.

[0028] In summary, the present invention has the following beneficial effects:

[0029] 1. When the recycled PET particles are melt-blended with POE-g-GMA, toughening agent, and polyethylene terephthalate-1,4-cyclohexanedimethanol, the polar groups contained in POE-g-GMA react with the terminal groups in the recycled PET and polyethylene terephthalate-1,4-cyclohexanedimethanol to form chemical bonds, thereby improving the compatibility and stability of the blend to a certain extent. Moreover, after the recycled PET particles are blended with polyethylene terephthalate-1,4-cyclohexanedimethanol, the molecular chains intersperse and entangle with each other, thereby effectively enhancing the impact resistance of the recycled PET material.

[0030] 2. When phosphorus-nitrogen intumescent flame retardant and diethyl zinc hypophosphite are used in combination, the carbon layer formed when the phosphorus-nitrogen intumescent flame retardant burns can provide attachment points for diethyl zinc phosphate, enabling it to better adhere to the surface of the polymer, while the protective barrier formed by diethyl zinc phosphate can further enhance the stability of the carbon layer formed when the phosphorus-nitrogen intumescent flame retardant burns, effectively improving the flame retardant effect of the recycled PET material. DETAILED DESCRIPTION

[0031] The present invention is further described in detail below with reference to the embodiments.

[0032] A halogen-free flame-retardant recycled PET material for steel coil packaging comprises the following raw materials in parts by weight: 100 parts of recycled PET, 5-10 parts of POE-g-GMA, 4-8 parts of a toughening agent, 15-20 parts of polyethylene terephthalate-1,4-cyclohexanedimethanol, 3-7 parts of a flame retardant, 1-3 parts of a stabilizer, and 0.3-0.5 parts of an antioxidant.

[0033] In one embodiment of the present application, the recycled PET is obtained by the following modification method, which comprises the following steps: drying the recycled PET particles, adding a silane coupling agent, mixing, melt extruding, cooling and pelletizing to obtain modified recycled PET, wherein the amount of the silane coupling agent added is 4-8% of the weight of the recycled PET.

[0034] In one embodiment of the present application, the silane coupling agent is triethoxypropyl isocyanate silane.

[0035] In one embodiment of the present application, the toughening agent is obtained by the following preparation method:

[0036] S1. Mix 5 parts of butyl acrylate, 0.2 parts of propyl methacrylate, 0.5 parts of surfactant, 0.05 parts of ammonium persulfate, 0.05 parts of sodium bicarbonate and 30 parts of water by weight, and react at a temperature of 75±3°C for 30 minutes to obtain an emulsion;

[0037] S2. Add 5 parts of polyurethane prepolymer dropwise to the emulsion obtained in step S1 and add 0.35 parts of ammonium persulfate at the same time, react for 2 hours, cool, discharge and dry to obtain a toughening agent.

[0038] In one embodiment of the present application, the raw material further includes 2-5 parts of nano-wollastonite whiskers.

[0039] In one embodiment of the present application, the nano-wollastonite whiskers are modified nano-wollastonite whiskers, and the modification is obtained by the following method:

[0040] (1) Nano-wollastonite whiskers were ultrasonically dispersed in N,N-dimethylformamide, and then dimethylaminopyridine was added at 85°C and reacted at this temperature for 1 hour;

[0041] (2) adding dodecyl succinic anhydride dropwise to the reactant obtained in step (1), stirring the reaction for 4 hours after the addition is completed, and then cooling, washing, and drying the reactant to obtain modified nano-wollastonite whiskers.

[0042] In one embodiment of the present application, the flame retardant is composed of a phosphorus-nitrogen intumescent flame retardant and diethyl zinc hypophosphite in a weight ratio of 1:(0.2-0.6).

[0043] In one embodiment of the present application, the phosphorus-nitrogen intumescent flame retardant is obtained by the following preparation method: 2-carboxyethylphenyl hypophosphorous acid and melamine in a molar ratio of 1:1 are added to water, the reaction is stirred at room temperature for 4.5-5 hours, the precipitate is filtered and washed, vacuum dried at 80±5°C for 5-6 hours, and heated at 160±5°C for 5 hours to obtain a white powder, which is washed again and vacuum dried at 80±5°C for 5-6 hours to obtain the phosphorus-nitrogen intumescent flame retardant.

[0044] In one embodiment of the present application, the stabilizer is methyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate.

[0045] In one embodiment of the present application, the antioxidant is any one of dilauryl thiodipropionate and antioxidant 300, and the effects that can be achieved are basically the same.

[0046] A method for preparing a halogen-free flame-retardant recycled PET material for steel coil packaging comprises the following steps: mixing recycled PET, POE-g-GMA, polyethylene terephthalate-1,4-cyclohexanedimethanol, a flame retardant, a stabilizer and an antioxidant, and then melt-extruding to obtain the halogen-free flame-retardant recycled PET material.

[0047] Preparation Example 1.1

[0048] The modified method of recycled PET comprises the following steps: drying recycled PET particles at 120°C for 3 hours, adding isocyanate propyl triethoxy silane, mixing, and then adding to a twin-screw extruder for melt extrusion, the screw temperature is 250-255°C, cooling and pelletizing to obtain modified recycled PET, wherein the amount of isocyanate propyl triethoxy silane added is 4% of the weight of the recycled PET.

[0049] Preparation Example 1.2

[0050] The modified method of recycled PET comprises the following steps: drying recycled PET particles at 120° C. for 3 hours, adding isocyanate propyl triethoxy silane, mixing, and then adding to a twin-screw extruder for melt extrusion, the screw temperature is 250-255° C., cooling and pelletizing to obtain modified recycled PET, wherein the amount of isocyanate propyl triethoxy silane added is 6% of the weight of the recycled PET.

[0051] Preparation Example 1.3

[0052] The modified method of recycled PET comprises the following steps: drying recycled PET particles at 120° C. for 3 hours, adding isocyanate propyl triethoxy silane, mixing, and then adding to a twin-screw extruder for melt extrusion, the screw temperature is 250-255° C., cooling and pelletizing to obtain modified recycled PET, wherein the amount of isocyanate propyl triethoxy silane added is 8% of the weight of the recycled PET.

[0053] Comparative Preparation Example 1.3

[0054] The modified method of recycled PET is to use an equal amount of γ-aminopropyltrimethoxysilane to replace isocyanatepropyltriethoxysilane, and the rest is the same as that in Preparation Example 1.3.

[0055] Preparation Example 2

[0056] The preparation method of the toughening agent comprises the following steps:

[0057] S1. Mix 500 g of butyl acrylate, 20 g of propyl methacrylate, 50 g of a surfactant, 5 g of ammonium persulfate, 5 g of sodium bicarbonate and 3000 g of water by weight, and react at a temperature of 75 ± 3 ° C for 30 min to obtain an emulsion;

[0058] S2, dropwise add 500g of polyurethane prepolymer into the emulsion obtained in step S1 and then add 35g of ammonium persulfate, react for 2h, cool, discharge and dry to obtain a toughening agent.

[0059] Preparation Example 3

[0060] The modification method of nano-wollastonite whiskers comprises the following steps:

[0061] (1) Ultrasonic dispersion of nano-wollastonite whiskers in N,N-dimethylformamide to form a slurry with a concentration of about 10 wt%, and then adding dimethylaminopyridine at 85° C. to react at this temperature for 1 hour, wherein the amount of dimethylaminopyridine added is 12.5% ​​of the mass of the nano-wollastonite whiskers;

[0062] (2) adding dodecyl succinic anhydride dropwise to the reactant obtained in step (1), stirring the reaction for 4 hours after the addition is completed, and then cooling, washing, and drying the reactant to obtain modified nano-wollastonite whiskers, wherein the weight ratio of dodecyl succinic anhydride to nano-wollastonite whiskers is 6:1.

[0063] Preparation Example 4.1

[0064] The preparation method of a phosphorus-nitrogen intumescent flame retardant comprises the following steps: adding 1 mol of 2-carboxyethylphenyl hypophosphorous acid and 1 mol of melamine into 500 mL of water, stirring the reaction at room temperature for 4.5 hours, filtering the precipitate for washing, vacuum drying at 80°C for 5.5 hours, heating at 160°C for 5 hours to obtain a white powder, washing again, and vacuum drying at 80°C for 5.5 hours to obtain the phosphorus-nitrogen intumescent flame retardant.

[0065] Preparation Example 4.2

[0066] The preparation method of a phosphorus-nitrogen intumescent flame retardant comprises the following steps: adding 1 mol of 2-carboxyethylphenyl hypophosphorous acid and 1 mol of melamine into 500 mL of water, stirring the reaction at room temperature for 4.5 hours, filtering the precipitate for washing, vacuum drying at 75°C for 6 hours, heating at 155°C for 5 hours to obtain a white powder, washing again, and vacuum drying at 75°C for 6 hours to obtain the phosphorus-nitrogen intumescent flame retardant.

[0067] Preparation Example 4.3

[0068] The preparation method of a phosphorus-nitrogen intumescent flame retardant comprises the following steps: adding 1 mol of 2-carboxyethylphenyl hypophosphorous acid and 1 mol of melamine into 500 mL of water, stirring the reaction at room temperature for 5 hours, filtering the precipitate for washing, vacuum drying at 85°C for 5 hours, heating at 165°C for 5 hours to obtain a white powder, washing again, and vacuum drying at 85°C for 5 hours to obtain the phosphorus-nitrogen intumescent flame retardant.

[0069] Example 1

[0070] A method for preparing a halogen-free flame-retardant recycled PET material for steel coil packaging comprises the following steps: drying the recycled PET at 120° C. for 2 hours, taking 10 kg of the recycled PET, 0.5 kg of POE-g-GMA (with a grafting rate of 1% and a melt index of 0.5-3 g / 10 min), 0.4 kg of a toughening agent obtained in Preparation Example 2, 1.5 kg of polyethylene terephthalate-1,4-cyclohexanedimethanol, 0.3 kg of a flame retardant zinc diethylphosphite, 0.1 kg of a stabilizer 3-(3,5-di-tert-butyl-4-hydroxyphenyl)methyl propionate and 0.03 kg of dilauryl thiodipropionate, stirring and mixing, adding the mixture into a twin-screw extruder for melt extrusion, the screw temperature being 245-250° C., cooling and pelletizing to obtain the halogen-free flame-retardant recycled PET material.

[0071] Example 2

[0072] A method for preparing a halogen-free flame-retardant recycled PET material for steel coil packaging comprises the following steps: drying the recycled PET at 120° C. for 2 hours, taking 10 kg of recycled PET, 0.8 kg of POE-g-GMA (with a grafting rate of 1% and a melt index of 0.5-3 g / 10 min), 0.6 kg of a toughening agent obtained in Preparation Example 2, 1.8 kg of polyethylene terephthalate-1,4-cyclohexanedimethanol, 0.3 kg of a flame retardant zinc diethylphosphite, 0.1 kg of a stabilizer 3-(3,5-di-tert-butyl-4-hydroxyphenyl)methyl propionate and 0.03 kg of dilauryl thiodipropionate, stirring and mixing, adding the mixture into a twin-screw extruder for melt extrusion, the screw temperature being 245-250° C., cooling and pelletizing to obtain the halogen-free flame-retardant recycled PET material.

[0073] Example 3

[0074] A method for preparing a halogen-free flame-retardant recycled PET material for steel coil packaging comprises the following steps: drying the recycled PET at 120° C. for 2 hours, taking 10 kg of the recycled PET, 1 kg of POE-g-GMA (with a grafting rate of 1% and a melt index of 0.5-3 g / 10 min), 0.8 kg of a toughening agent obtained in Preparation Example 2, 2 kg of polyethylene terephthalate-1,4-cyclohexanedimethanol, 0.3 kg of a flame retardant zinc diethylphosphite, 0.1 kg of a stabilizer 3-(3,5-di-tert-butyl-4-hydroxyphenyl)methyl propionate and 0.03 kg of dilauryl thiodipropionate, stirring and mixing, adding the mixture into a twin-screw extruder for melt extrusion, the screw temperature being 245-250° C., cooling and pelletizing to obtain the halogen-free flame-retardant recycled PET material.

[0075] Example 4

[0076] A method for preparing a halogen-free flame-retardant recycled PET material for steel coil packaging comprises the following steps: drying the recycled PET at 120° C. for 2 hours, taking 10 kg of recycled PET, 0.8 kg of POE-g-GMA (with a grafting rate of 1% and a melt index of 0.5-3 g / 10 min), 0.6 kg of a toughening agent obtained in Preparation Example 2, 1.8 kg of polyethylene terephthalate-1,4-cyclohexanedimethanol, 0.5 kg of a flame retardant zinc diethylphosphite, 0.2 kg of a stabilizer 3-(3,5-di-tert-butyl-4-hydroxyphenyl)methyl propionate and 0.04 kg of dilauryl thiodipropionate, stirring and mixing, adding the mixture into a twin-screw extruder for melt extrusion, the screw temperature being 245-250° C., cooling and pelletizing to obtain the halogen-free flame-retardant recycled PET material.

[0077] Comparative Example 4

[0078] A method for preparing a halogen-free flame-retardant recycled PET material for steel coil packaging, which is different from Example 4 in that a commercially available PET toughening agent with a CAS number of 112-84-5 is used as a toughening agent, and the rest is the same as Example 4.

[0079] Example 5

[0080] A preparation method of a halogen-free flame-retardant recycled PET material for steel coil packaging comprises the following steps: drying the recycled PET at 120° C. for 2 hours, taking 10 kg of recycled PET, 0.8 kg of POE-g-GMA (with a grafting rate of 1% and a melt index of 0.5-3 g / 10 min), 0.6 kg of a toughening agent obtained in Preparation Example 2, 1.8 kg of polyethylene terephthalate-1,4-cyclohexanedimethanol, 0.7 kg of a flame retardant zinc diethylphosphite, 0.3 kg of a stabilizer 3-(3,5-di-tert-butyl-4-hydroxyphenyl)methyl propionate and 0.05 kg of dilauryl thiodipropionate, stirring and mixing, adding the mixture into a twin-screw extruder for melt extrusion, the screw temperature being 245-250° C., cooling and pelletizing to obtain the halogen-free flame-retardant recycled PET material.

[0081] Example 6

[0082] A method for preparing a halogen-free flame-retardant recycled PET material for steel coil packaging, which is different from Example 4 in that the recycled PET adopts the modified recycled PET obtained in Preparation Example 1.1, and the rest is the same as Example 4.

[0083] Example 7

[0084] A method for preparing a halogen-free flame-retardant recycled PET material for steel coil packaging, which is different from Example 4 in that the recycled PET uses the modified recycled PET obtained in Preparation Example 1.2, and the rest is the same as Example 4.

[0085] Example 8

[0086] A method for preparing a halogen-free flame-retardant recycled PET material for steel coil packaging, which is different from Example 4 in that the recycled PET adopts the modified recycled PET obtained in Preparation Example 1.3, and the rest is the same as Example 4.

[0087] Comparative Example 8

[0088] A method for preparing a halogen-free flame-retardant recycled PET material for steel coil packaging, which is different from Example 8 in that the recycled PET uses the modified recycled PET obtained in Comparative Preparation Example 1.3, and the rest is the same as Example 8.

[0089] Example 9

[0090] A method for preparing a halogen-free flame-retardant recycled PET material for steel coil packaging, which is different from Example 6 in that the raw material of the recycled PET also includes 0.2 kg of nano wollastonite whiskers, and the rest is the same as Example 6.

[0091] Example 10

[0092] A method for preparing a halogen-free flame-retardant recycled PET material for steel coil packaging, which is different from Example 6 in that the raw material of the recycled PET also includes 0.4 kg of nano wollastonite whiskers, and the rest is the same as Example 6.

[0093] Embodiment 11

[0094] A method for preparing a halogen-free flame-retardant recycled PET material for steel coil packaging, which is different from Example 6 in that the raw material of the recycled PET also includes 0.5 kg of nano wollastonite whiskers, and the rest is the same as Example 6.

[0095] Example 12

[0096] A method for preparing a halogen-free flame-retardant recycled PET material for steel coil packaging, which is different from Example 10 in that the nano-wollastonite whiskers are the nano-wollastonite whiskers modified by Preparation Example 3, and the rest are the same as Example 10.

[0097] Embodiment 13

[0098] A method for preparing a halogen-free flame-retardant recycled PET material for steel coil packaging, which is different from Example 12 in that the flame retardant uses the phosphorus-nitrogen intumescent flame retardant obtained in Preparation Example 4.1, and the rest is the same as Example 12.

[0099] Embodiment 14

[0100] A method for preparing a halogen-free flame-retardant recycled PET material for steel coil packaging, which is different from Example 12 in that the flame retardant uses the phosphorus-nitrogen intumescent flame retardant obtained in Preparation Example 4.2, and the rest is the same as Example 12.

[0101] Embodiment 15

[0102] A method for preparing a halogen-free flame-retardant recycled PET material for steel coil packaging, which is different from Example 12 in that the flame retardant uses the phosphorus-nitrogen intumescent flame retardant obtained in Preparation Example 4.3, and the rest is the same as Example 12.

[0103] Example 16

[0104] A method for preparing a halogen-free flame-retardant recycled PET material for steel coil packaging, which is different from Example 12 in that the total amount of flame retardant is 0.5 kg, and the flame retardant is composed of the phosphorus-nitrogen intumescent flame retardant obtained in Preparation Example 4.1 and diethyl zinc hypophosphite in a weight ratio of 1:0.2, and the rest is the same as Example 12.

[0105] Embodiment 17

[0106] A method for preparing a halogen-free flame-retardant recycled PET material for steel coil packaging, which is different from Example 12 in that the total amount of flame retardant is 0.5 kg, and the flame retardant is composed of the phosphorus-nitrogen intumescent flame retardant obtained in Preparation Example 4.1 and diethyl zinc hypophosphite in a weight ratio of 1:0.4, and the rest is the same as Example 12.

[0107] Embodiment 18

[0108] A method for preparing a halogen-free flame-retardant recycled PET material for steel coil packaging, which is different from Example 12 in that the total amount of flame retardant is 0.5 kg, and the flame retardant is composed of the phosphorus-nitrogen intumescent flame retardant obtained in Preparation Example 4.1 and diethyl zinc hypophosphite in a weight ratio of 1:0.6, and the rest is the same as Example 12.

[0109] Embodiment 19

[0110] A method for preparing a halogen-free flame-retardant recycled PET material for steel coil packaging, which is different from Example 17 in that the total amount of flame retardant is 0.5 kg, and the flame retardant is composed of the phosphorus-nitrogen expandable flame retardant obtained in Preparation Example 4.1 and ammonium polyphosphate in a weight ratio of 1:0.4, and the rest is the same as Example 17.

[0111] Comparative Example 1

[0112] A method for preparing a halogen-free flame-retardant recycled PET material for steel coil packaging, which is different from Example 4 in that an equal amount of POE-g-MAH (grafting rate ≥ 0.8%, melt index 0.8-2.0g / 10min) is used instead of POE-g-GMA, and the rest is the same as Example 4.

[0113] Comparative Example 2

[0114] A method for preparing a halogen-free flame-retardant recycled PET material for steel coil packaging, which is different from Example 4 in that there is no polyethylene terephthalate-1,4-cyclohexanedimethanol in the raw material, and the rest is the same as Example 4.

[0115] Comparative Example 3

[0116] A method for preparing a halogen-free flame-retardant recycled PET material for steel coil packaging, which is different from Example 4 in that there is no toughening agent in the raw material, and the rest is the same as Example 4.

[0117] Comparative Example 4

[0118] A method for preparing a halogen-free flame-retardant recycled PET material for steel coil packaging, which is different from Example 4 in that there is no POE-g-GMA in the raw material, and the rest is the same as Example 4.

[0119] Comparative Example 5

[0120] A method for preparing a halogen-free flame-retardant recycled PET material for steel coil packaging, which is different from Example 4 in that there is no polyethylene terephthalate-1,4-cyclohexanedimethanol ester and toughening agent in the raw materials, and the rest is the same as Example 4.

[0121] Comparative Example 6

[0122] A method for preparing a halogen-free flame-retardant recycled PET material for steel coil packaging, which is different from Example 4 in that there is no polyethylene terephthalate-1,4-cyclohexanedimethanol ester and POE-g-GMA in the raw materials, and the rest is the same as Example 4.

[0123] Comparative Example 7

[0124] A method for preparing a halogen-free flame-retardant recycled PET material for steel coil packaging, which is different from Example 4 in that there is no toughening agent and POE-g-GMA in the raw material, and the rest is the same as Example 4.

[0125] Comparative Example 8

[0126] A method for preparing a halogen-free flame-retardant recycled PET material for steel coil packaging, which is different from Example 4 in that an equal amount of ethylene-methyl acrylate-glycidyl methacrylate random terpolymer is used instead of polyethylene terephthalate-1,4-cyclohexanedimethanol, and the rest is the same as Example 4.

[0127] Comparative Example 9

[0128] A method for preparing a halogen-free flame-retardant recycled PET material for steel coil packaging, which is different from Example 4 in that there is no stabilizer 3-(3,5-di-tert-butyl-4-hydroxyphenyl) methyl propionate in the raw material, and the rest is the same as Example 4.

[0129] Performance Testing

[0130] The flame retardant properties and mechanical properties of the halogen-free flame retardant recycled PET materials obtained in the above examples and comparative examples were tested, and the test results are shown in Table 1.

[0131] The mechanical properties tests are as follows: impact strength (cantilever beam method) is tested in accordance with the relevant provisions of GB / T1843-2008; tensile properties are tested in accordance with the relevant provisions of GB / T1040.2-2006, with a tensile rate of 50 mm / min; bending properties are tested in accordance with the relevant provisions of GB / T9341-2008, with a bending rate of 2 mm / min. All tests are carried out at room temperature, and each sample is tested repeatedly for 5 specimens.

[0132] Table 1 Test results of recycled PET materials

[0133]

[0134]

[0135] From Table 1 we can see that:

[0136] In Examples 1-3 of the present application, when the addition amounts of flame retardants, stabilizers and antioxidants remain unchanged, after gradually increasing the addition amounts of POE-g-GMA, toughening agents and polyethylene terephthalate-1,4-cyclohexanedimethanol, the tensile strength, elongation at break, impact strength and flexural strength of the recycled PET materials obtained in Examples 1-3 all show an increasing trend. However, after reaching the addition amount of Example 3, the growth rate of each data decreases, and the tensile strength and impact strength are lower than those in Example 2. It can be seen that when the addition amounts of POE-g-GMA, toughening agents and polyethylene terephthalate-1,4-cyclohexanedimethanol are within the range specified in the present application, the impact resistance and tensile properties of the recycled PET material can be effectively guaranteed.

[0137] Compared with Example 2, Example 4-5 increases the amount of flame retardant, stabilizer and antioxidant added on the basis of Example 2. The oxygen index of the recycled PET material obtained in Example 4-5 is higher than that in Example 2, and the other mechanical properties are basically the same as those in Example 2.

[0138] Compared with Example 4, after using the commercially available PET toughening agent, the tensile strength, impact strength, etc. obtained in Comparative Example 4 are lower than those in Example 4. It can be seen that after using the toughening agent obtained in the present application, its combination with other raw materials effectively improves the impact resistance of the recycled PET.

[0139] Compared with Example 4, when the recycled PET particles are modified with isocyanatepropyltriethoxysilane, the tensile strength, elongation at break, impact strength and flexural strength of the recycled PET materials obtained in Examples 6-8 are all increased compared with those in Example 4, indicating that the impact resistance and tensile properties of the recycled PET materials can be improved after the recycled PET particles are modified with isocyanatepropyltriethoxysilane.

[0140] Comparative Example 8 Compared with Example 8, when the recycled PET particles are modified with γ-aminopropyltrimethoxysilane instead of isocyanatepropyltriethoxysilane, the tensile strength, elongation at break, impact strength and flexural strength of the recycled PET material obtained in Comparative Example 8 are all reduced compared with those in Example 8. It can be seen that the tensile properties and impact resistance of the recycled PET material obtained by modifying the recycled PET particles with isocyanatepropyltriethoxysilane are better.

[0141] Compared with Example 6, as the amount of nano-wollastonite whiskers added increases, the tensile strength and flexural strength of the recycled PET materials obtained in Examples 9-11 increase with the increase in the amount of nano-wollastonite whiskers added, while the elongation at break and the impact strength first increase and then decrease, and the elongation at break and the impact strength of the recycled PET material obtained in Example 11 decrease significantly compared with those in the examples, indicating that the addition of excessive nano-wollastonite whiskers will greatly reduce the impact resistance of the recycled PET material. Therefore, after limiting the amount of nano-wollastonite whiskers added within the scope of the present application, it can effectively ensure that the recycled PET material has good tensile properties and impact resistance.

[0142] Compared with Example 10, when the nano-wollastonite whiskers are modified, the impact resistance of the recycled PET material can be further improved.

[0143] Compared with Example 12, when the flame retardant used in Examples 13-15 is a phosphorus-nitrogen expandable flame retardant, the oxygen index of the recycled PET material obtained in Examples 13-15 is further increased compared with that in Example 12.

[0144] Compared with Example 12, when the flame retardant is a mixture of a phosphorus-nitrogen intumescent flame retardant and diethyl zinc hypophosphite, the flame retardant properties of the recycled PET materials obtained in Examples 16-18 are significantly improved compared with those in Example 12. It can be seen that the combination of the phosphorus-nitrogen intumescent flame retardant and diethyl zinc hypophosphite effectively improves the flame retardant properties of the recycled PET material.

[0145] The difference between Example 19 and Example 17 is that when the flame retardant is composed of a phosphorus-nitrogen expandable flame retardant and ammonium polyphosphate, the oxygen index of the recycled PET material obtained in Example 19 is lower than that in Example 17, indicating that when the phosphorus-nitrogen expandable flame retardant is mixed with diethyl zinc hypophosphite, the flame retardant properties of the recycled PET material can be more effectively improved.

[0146] Compared with Example 4, when an equal amount of POE-g-MAH is used instead of POE-g-GMA, the tensile strength, elongation at break, impact strength and flexural strength of the recycled PET material obtained in Comparative Example 1 are all lower than those in Example 4. It can be seen that the combination of POE-g-GMA with recycled PET particles and polyethylene terephthalate-1,4-cyclohexanedimethanol can effectively improve the tensile properties and impact resistance of the recycled PET material.

[0147] Compared with Example 4, when polyethylene terephthalate-1,4-cyclohexanedimethanol is lacking in the raw material, the tensile strength, elongation at break, impact strength and flexural strength of the recycled PET material obtained in Comparative Example 2 are also reduced compared with Example 4; compared with Example 4, when the toughening agent is lacking in the raw material, the tensile strength and flexural strength of Comparative Example 3 are reduced compared with Example 4; compared with Example 4, when POE-g-GMA is lacking in the raw material, the mechanical properties of the recycled PET obtained in Comparative Example 4 are reduced. It can be seen that the use of the toughening agent in combination with polyethylene terephthalate-1,4-cyclohexanedimethanol and POE-g-GMA can effectively ensure the tensile properties and impact resistance of the recycled PET material.

[0148] Compared with Example 4, when there is no polyethylene terephthalate-1,4-cyclohexanedimethanol ester and toughening agent or no polyethylene terephthalate-1,4-cyclohexanedimethanol ester and POE-g-GMA or no toughening agent and POE-g-GMA in the raw materials, the various properties of the recycled PET obtained in Comparative Examples 5-7 are significantly reduced compared with those in Example 4. This further illustrates that the combination of polyethylene terephthalate-1,4-cyclohexanedimethanol ester, toughening agent and POE-g-GMA effectively improves the mechanical properties of the recycled PET material.

[0149] Compared with Example 4, when an equal amount of ethylene-methyl acrylate-glycidyl methacrylate random terpolymer is used to replace polyethylene terephthalate-1,4-cyclohexanedimethanol, the tensile strength, elongation at break, impact strength and flexural strength of the recycled PET material obtained in Comparative Example 8 are all lower than those in Example 4, which can further illustrate that the combined use of polyethylene terephthalate-1,4-cyclohexanedimethanol with POE-g-GMA and a toughening agent can effectively improve the impact resistance and tensile properties of the recycled PET material.

[0150] Compared with Example 4, when the raw material lacks the stabilizer, the mechanical properties of the recycled PET material obtained in Comparative Example 8 are all lower than those in Example 4, indicating that the addition of the stabilizer can effectively ensure the mechanical properties of the recycled PET material.

[0151] The embodiments of this specific implementation method are all preferred embodiments of the present invention, and are not intended to limit the protection scope of the present invention. Therefore, all equivalent changes made based on the structure, shape, and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A halogen-free flame-retardant recycled PET material for steel coil packaging, characterized in that: The invention comprises the following raw materials in parts by weight: 100 parts of recycled PET, 5-10 parts of POE-g-GMA, 4-8 parts of toughening agent, 15-20 parts of polyethylene terephthalate-1,4-cyclohexanedimethanol, 3-7 parts of flame retardant, 1-3 parts of stabilizer and 0.3-0.5 parts of antioxidant.

2. The halogen-free flame-retardant recycled PET material for steel coil packaging according to claim 1, characterized in that: The recycled PET is obtained by the following modification method, which comprises the following steps: drying the recycled PET particles, adding a silane coupling agent, mixing, melt extruding, cooling and pelletizing to obtain modified recycled PET, wherein the amount of the silane coupling agent added is 4-8% of the weight of the recycled PET.

3. The halogen-free flame-retardant recycled PET material for steel coil packaging according to claim 2, characterized in that: The silane coupling agent is isocyanate propyl triethoxy silane.

4. The halogen-free flame-retardant recycled PET material for steel coil packaging according to claim 1, characterized in that: The toughening agent is obtained by the following preparation method: S1. Mix 5 parts of butyl acrylate, 0.2 parts of propyl methacrylate, 0.5 parts of surfactant, 0.05 parts of ammonium persulfate, 0.05 parts of sodium bicarbonate and 30 parts of water by weight, and react at a temperature of 75±3°C for 30 minutes to obtain an emulsion; S2. Add 5 parts of polyurethane prepolymer dropwise to the emulsion obtained in step S1 and add 0.35 parts of ammonium persulfate at the same time, react for 2 hours, cool, discharge and dry to obtain a toughening agent.

5. The halogen-free flame-retardant recycled PET material for steel coil packaging according to claim 1, characterized in that: The raw materials also include 2-5 parts of nano-wollastonite whiskers.

6. The halogen-free flame-retardant recycled PET material for steel coil packaging according to claim 5, characterized in that: The nano-wollastonite whiskers are modified nano-wollastonite whiskers, and the modification is obtained by the following method: (1) Nano-wollastonite whiskers were ultrasonically dispersed in N,N-dimethylformamide, and then dimethylaminopyridine was added at 85° C. and reacted at this temperature for 1 h; (2) adding dodecyl succinic anhydride dropwise to the reactant obtained in step (1), stirring the reaction for 4 hours after the addition is completed, and then cooling, washing, and drying the reactant to obtain modified nano-wollastonite whiskers.

7. The halogen-free flame-retardant recycled PET material for steel coil packaging according to claim 1, characterized in that: The flame retardant is composed of a phosphorus-nitrogen expansion flame retardant and diethyl zinc hypophosphite in a weight ratio of 1:(0.2-0.6).

8. The halogen-free flame-retardant recycled PET material for steel coil packaging according to claim 7, characterized in that: The phosphorus-nitrogen intumescent flame retardant is obtained by the following preparation method: 2-carboxyethylphenyl hypophosphorous acid and melamine in a molar ratio of 1:1 are added to water, stirred for reaction at room temperature for 4.5-5 hours, the precipitate is filtered for washing, vacuum dried at 80±5°C for 5-6 hours, heated at 160±5°C for 5 hours to obtain a white powder, washed again, and vacuum dried at 80±5°C for 5-6 hours to obtain the phosphorus-nitrogen intumescent flame retardant.

9. The halogen-free flame-retardant recycled PET material for steel coil packaging according to claim 1, characterized in that: The stabilizer is 3-(3,5-di-tert-butyl-4-hydroxyphenyl) methyl propionate, and the antioxidant is one of dilauryl thiodipropionate and antioxidant 300.

10. A method for preparing the halogen-free flame-retardant recycled PET material for steel coil packaging according to any one of claims 1 to 9, characterized in that: The method comprises the following steps: mixing recycled PET, POE-g-GMA, a toughening agent, polyethylene terephthalate-1,4-cyclohexanedimethanol, a flame retardant, a stabilizer and an antioxidant, and then melt-extruding the mixture to obtain a halogen-free flame-retardant recycled PET material.

Citation Information

Patent Citations

  • ABS / PET composite material and preparation method thereof

    CN104672751A

  • Halogen-free inflaming-retarding long glass fiber reinforced PET (Polyethylene Terephthalate) composite material and preparation method thereof

    CN106398137A

  • Special halogen-free flame-retardant recycled PET (polyethylene terephthalate) sheet material for coil packaging and preparation method thereof

    CN109735065A

  • Cold-resistant weather-resistant low-odor glass fiber reinforced composite material and preparation method thereof

    CN110256797A

  • Economic cold-resistant low-smell glass fiber reinforced composite material and preparation method thereof

    CN110256823A

Cited By

  • Micro-crosslinked high-molecular-weight high-heat-resistance brominated epoxy resin and preparation method thereof

    CN120795283A